A critical review of the Iranian National Olympic Committee’s performance in designing the opening parade costumes: signs of inefficiency and damage to the national identity - Kiani, Mohammad Saeid (Quality in Sport, 2024)
This research aims to evaluate and critique the performance of the Iranian National Olympic Committee in designing the costumes for the Olympic opening parade. The study seeks to identify the strengths and weaknesses of these designs and compare them with successful global examples to help improve future designs. A review method was used to achieve this goal. This method involved examining previous research related to the design of Olympic uniforms and the criticisms they received. The analysis included public and media critiques, athlete surveys, and an examination of the characteristics of successful international designs.The findings indicate that Iran’s Olympic uniforms have struggled to make a positive impact internationally due to weaknesses in aligning with global standards, a lack of attention to cultural symbols, and inadequate use of modern technologies. Compared to successful global designs, these uniforms have faced challenges in representing national identity and effectively communicating with audiences. The study concludes that to improve future designs, the Iranian National Olympic Committee should focus on enhancing collaboration with cultural and social experts, using international consultants to align with global standards, and establishing continuous evaluation processes to identify and address weaknesses. Additionally, developing specialized teams and providing training for designers are recommended to improve design quality and elevate national prestige on the international stage.